Microbial Remediation of Textile Dye Acid Orange by a Novel Bacterial Consortium SPB92 - Bera, Sweta Parimita; Shah, Maulin P.; Godhaniya, Manoj (Frontiers in Environmental Science, 2022)
Textile effluent generated during the dyeing process of textiles is a huge supplier to water toxicity all over the world. Textile dyes are the main toxic component found in the effluent sample which is difficult to treat. A bacterial consortium capable of decolourizing and degrading the textile dye acid orange is reported in this research article. The bacterial consortium was identified by 16S rDNA sequence and phenotypic characteristics. It is composed of four strains i.e. Pseudomonas stutzeri (MW219251), Bacillus tequilensis (MW110471), Bacillus flexus (MW131645), Kocuria rosea (MW132411). The consortium was able to cause decolorization of azo dye acid orange (30 mg/L) in 23 h, when kept under static laboratory conditions. The optimal pH and temperature for color removal were pH 7.5 and 32° C, respectively. The decolorization of dye before and after was checked by UV-Visible absorption spectra. This gives evidence that decolorization was caused due to biodegradation. This was further assured by studying the reduction of biological oxygen demand (BOD0 (96%), chemical oxygen demand (COD) (79%), and TOC (total organic carbon) (54%) of the bacterial-treated water sample. The Fourier transform-infrared spectroscopy (FT-IR) spectroscopy and gas chromatography-mass spectroscopy (GC-MS) results confirmed the mineralization of the dye. The results indicate the effectiveness of the bacterial consortium SPB92 in the biodegradation of acid orange dye. This demonstrates that the consortium has immense potential and will serve as an important contributor to the treatment of textile wastewater.